High-temperature corrosion resistance of nickel-base alloy 617 in supercritical carbon dioxide environment - Zhiyuan Liang; Yong Gui; Qinxin Zhao (Materials Research Express, 2020)
Corrosion behavior of Inconel 617 in supercritical carbon dioxide at 650 °C and 15 MPa for 1000 h was investigated. X-ray diffraction, high-resolution transmission microscopy, and Raman spectrum were used to observe and analyze the corrosion products formed on Inconel 617. The results showed that the corrosion products formed on Inconel 617 were composed of a thick Cr _2 O _3 layer, a thin Al _2 O _3 layer and a carbon-penetrated zone from the interface between carbon dioxide and the oxide scale to the substrate. Carbon was deposited on the surface of the oxide scales, which was verified by Raman results. The oxidation of Inconel 617 suffered in supercritical carbon dioxide was more serious than the carburization of Inconel 617.